Edukasi Corona Virus Disease dan Pencegahannya Pada Siswa TK Nurul Izzah di Desa Candirejo Ungaran Barat Kabupaten Semarang - Puji Astuti, Ana; Haryani, Siti; Sari, Kartika (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2021)
Corona virus Disease 2019 (COVID-19) is an infectious disease that’s caused by a new type of coronavirus. The disease began with the emergence of a known case of penumonia in Wuhan, China at the end of December 2019 (Li et al, 2020). The disease eventually became a  pandemic problem around the word, including Indonesia. The purpose of this community service activities are to increase the knowledge of kindergarten students about covid-19 disease and it’s prevention, so that it can prevent transmission and increased cased of covid-19. Method of implementation of activities are carried out several stages, namely location obeservation and socialization of health education activities about corona virus. This is health education about its prevention and motivation of students and demonstration of washing hands properly. The result of community service activities are  health education about covid-19, disease prevention of covid-19 and demonstration of correct hand washing steps attended by 31,57% of kindergarten students of Nurul Izzah school with 24 students devided into several small groups. Students can explain about coronavirus disease, this is and its prevention and demonstrate how to wash hands properly step as much as 100%. Based on the result of community service activities need to be followed up is the provision of education canbe given to all students in order to suppress the decreased inthe number of incidents confirmed positively cover cases of covid-19 ang Semarang district area especially green zona.AbstrakCoronavirus Disease 2019 (COVID-19) merupakan penyakit menular yang disebabkan oleh Coronavirus jenis baru. Penyakit ini diawali dengan munculnya kasus pneumonia yang tidak diketahui etiologinya di Wuhan, China pada akhir Desember 2019 (Li et al, 2020). Penyakit ini pada akhirnya menjadi masalah pandemi di seluruh dunia, termasuk Indonesia. Tujuan kegiatan pengabdian kepada masyarakat ini adalah untuk meningkatkan pengetahuan siswa TK terkait penyakit covid-19 dan pencegahannya, sehingga harapannnya dapat mencegah penularan dan peningkatan kasus covid-19. Metode pelaksanaan kegiatan dilakukan beberapa tahap, yaitu observasi lokasi dan sosialisasi kegiatan, penyuluhan kesehatan tentang corona virus disease, penyuluhan kesehatan tentang pencegahannya dan motivasi siswa serta mendemonstrasikan mencuci tangan dengan benar. Hasil dari kegiatan ini adalah penyuluhan tentang penyakit covid-19 atau corona virus disease, pencegahan dan demonstrasi mencuci tangan yang benar langkah dihadiri oleh 31,57% siswa TK Nurul Izzah dengan sebanyak 24 siswa yang terbagi dalam beberapa kelompok kecil dan siswa dapat menjelaskan tentang corona virus disease, pencegahannya serta mendemonstrasikan cara mencuci tangan dengan benar langkah sebanyak 100%. Berdasarkan hasil kegiatan pengabdian perlu